2020
DOI: 10.2147/cmar.s225711
|View full text |Cite
|
Sign up to set email alerts
|

<p>High Preoperative Controlling Nutritional Status Score Predicts a Poor Prognosis in Patients with Localized Upper Tract Urothelial Cancer: A Propensity Score Matching Study in a Large Chinese Center</p>

Abstract: The aim of this study was to elucidate the prognostic value of the preoperative controlling nutritional status (CONUT) score, a new index based on the total lymphocyte count, serum albumin concentration and total cholesterol concentration, in patients with localized upper tract urothelial cancer (UTUC) after radical nephroureterectomy (RNU) using propensity score matching (PSM) analysis. Methods: We retrospectively reviewed 908 consecutive patients with localized UTUC who underwent RNU between 1999 and 2015. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…( 5 ) As a simple, economic and efficient screening tool to detect the nutritional status of inpatients without requiring extra skills, the CONUT score has been applied in many tumors for its prognostic value. ( 6 , 7 ) Recently, it was reported that the CONUT score was independently associated with the poor prognosis in many cardiovascular disease. ( 8 , 9 ) Recently, Restrepo and colleagues proposed a view that “pneumonia as a cardiovascular disease”.…”
Section: Introductionmentioning
confidence: 99%
“…( 5 ) As a simple, economic and efficient screening tool to detect the nutritional status of inpatients without requiring extra skills, the CONUT score has been applied in many tumors for its prognostic value. ( 6 , 7 ) Recently, it was reported that the CONUT score was independently associated with the poor prognosis in many cardiovascular disease. ( 8 , 9 ) Recently, Restrepo and colleagues proposed a view that “pneumonia as a cardiovascular disease”.…”
Section: Introductionmentioning
confidence: 99%
“…Excluded from 7 reviews, 7 letters, and comments, 3 studies were unable to extract data entirely, and 2 studies with low literature quality scores. 7 retrospective studies and 1 propensity matching scoring study with 2232 patients were included in this meta-analysis at last (Figure 1) (22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Description Of Studiesmentioning
confidence: 99%
“…8 studies reported the HR of the low CONUT group and the high CONUT group on OS, and a total of 2232 patients were enrolled (22)(23)(24)(25)(26)(27)(28)(29). After the heterogeneity test, the heterogeneity among the studies was within the acceptable range (I 2 = 45.6%, P=0.075), and the fixed-effects model was used to pool HR.…”
Section: Survival Outcomesmentioning
confidence: 99%
“…We initially identified 672 studies from the three databases mentioned above. Ten studies were ultimately included in this meta-analysis based on our inclusion and exclusion criteria (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). A total of 12,865 patients had UTUC, and 2045 (15.9%) had diabetes.…”
Section: Literature Screening and Quality Assessmentmentioning
confidence: 99%